Speech acts of apologies. (c2016) - Zeaiter, Lana Fouad (2016)
Many cross-cultural studies investigate the language of apology, also called speech act of apology. These studies among others uncover differences and similarities in different societies in the use of the language of apology. People apologize differently, depending on the situation, their age, their gender and their socio-cultural background. This study attempts to establish a pattern for expressing apology, by highlighting the commonly used expressions by Lebanese adults. It also investigates age and gender similarities and differences in the use of apology in the context of Lebanese restaurants. The data analyzed were participants’ responses to a discourse completion task and a questionnaire, in addition to restaurant managers’ responses to a series of questions. Data analysis revealed that there are no significant differences in the way males and females of different age groups apologize in restaurant related situations. Recommendations for further research on speech acts of apology are suggested.